A New Control Curve Method for Image Deformation - Hong-an Li; Jie Zhang; Lei Zhang; Baosheng Kang (Universitas Ahmad Dahlan, 2014)
Different from the direct deformation on the image,we propose a deformation method using wavelet filter and control curves. Firstly, the original image is filtered into a high-frequency subimage and a low-frequency subimage by the wavelet, and the low-frequency subimage is deformed use the moving least squares and the control curves.Then, the key points are set to create control curves according to shape information or deformation requirement, and moved to new position to deform the image using moving least squares. At last, the final deformation image can be obtained by adding the deformed low-frequency part to the high-frequency part. Experiments show that the proprosed method performs very well to preserve high-frequency detail information and describe the image shape and contour, so can obtain the satisfactory and realistic deformation results.